Natural hydraulic lime-based mortar as well as preparation method and application thereof
By using mortar prepared by natural hydraulic lime and other materials, the problem of poor compatibility between traditional cement-based materials and ancient buildings is solved, and the restoration effect of ancient buildings with high strength, low drying and shrinkage and excellent breathability is achieved, which is suitable for 3D printing technology.
Patent Information
- Application Number
- CN202411998326.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-08
AI Technical Summary
The existing cement-based materials have compatibility problems with ancient buildings, making it difficult to be suitable for ancient buildings restoration with 3D printing technology. Moreover, the strength of traditional gas-hard lime develops slowly, has a large drying and shrinkage, and has a high water demand, making it difficult to meet the requirements of rapid molding.
Natural hydraulic lime is used as the main component, combined with quartz sand, limestone powder, metakaolin, bentonite and other materials, and combined with polycarboxylic acid water reducing agent, redispersible latex powder, wood fiber and other admixtures, to prepare a natural hydraulic lime-based mortar with high strength, low drying and shrinkage and excellent breathability.
This mortar is highly compatible with ancient building base materials, avoiding the problems of poor compatibility and slow strength of traditional cement-based materials, and has excellent strength and other properties, and is suitable for ancient building restoration by 3D printing technology.
Smart Images

Figure BDA0005226989800000091
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of building materials, and in particular to a natural hydraulic lime-based mortar and a preparation method and application thereof. Background Art
[0002] There are many kinds of ancient buildings in my country, which are precious cultural heritages carrying rich history and traditions. After years of natural erosion and human damage, many ancient buildings have shown varying degrees of aging and damage, such as cracks, peeling and even collapse. Although traditional methods of repairing ancient buildings are effective, they are usually time-consuming, complex processes, and require extremely high professionalism. In contrast, 3D printing technology provides a fast and efficient means of repair, which is particularly suitable for the repair of ancient building parts with complex shapes. It can accurately replicate damaged structures and shorten construction time. However, conventional cement-based materials currently have serious compatibility issues with ancient buildings themselves, and have been proven by a large number of experimental studies and practical projects to be unsuitable for the restoration of ancient buildings using 3D printing technology.
[0003] Traditional air-hardening lime has good compatibility with ancient building substrates and is widely used in ancient building restoration. However, traditional air-hardening lime has slow strength development, large drying shrinkage, and high water demand, which makes it difficult to meet the requirements of rapid prototyping, limiting its application in 3D printing technology. In contrast, natural hydraulic lime has the advantages of both hydraulic and air-hardening properties, with faster strength development, smaller drying shrinkage, and excellent air permeability, and better compatibility with ancient building substrates, and is expected to be used in ancient building restoration in 3D printing technology.
[0004] Therefore, providing a building material based on natural hydraulic lime has broad application prospects for the restoration of ancient buildings using 3D printing technology. Summary of the invention
[0005] The object of the present invention is to provide a natural hydraulic lime-based mortar and a preparation method and application thereof in view of the deficiencies in the prior art.
[0006] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0007] The present invention provides a natural hydraulic lime-based mortar, which comprises a base material, an admixture, an additive and water;
[0008] The base material comprises the following components in mass fractions: 60-75% of natural hydraulic lime, 15-35% of quartz sand and 5-15% of limestone powder.
[0009] Preferably, the admixture comprises metakaolin and bentonite, the mass ratio of metakaolin to base material is 2-5:100, and the mass ratio of bentonite to base material is 1-3:100.
[0010] Preferably, the admixture comprises polycarboxylate water reducer, redispersible latex powder, wood fiber, starch ether, thixotropic lubricant and air entraining agent.
[0011] Preferably, the mass ratio of the polycarboxylate water-reducing agent to the base material is 0.1-0.3:100, the mass ratio of the redispersible latex powder to the base material is 1-3:100, the mass ratio of the wood fiber to the base material is 0.5-1.5:100, the mass ratio of the starch ether to the base material is 0.1-0.2:100, the mass ratio of the thixotropic lubricant to the base material is 0.2-0.3:100, and the mass ratio of the air entraining agent to the base material is 0.01-0.05:100.
[0012] Preferably, the particle size of quartz sand is 100-300 meshes, the particle size of metakaolin is 500-700 meshes, the particle size of bentonite is 250-400 meshes, and the length of wood fiber is 0.5-1.5 mm.
[0013] Preferably, the mass ratio of water to base material is 0.2-0.6:1.
[0014] The present invention also provides a method for preparing the natural hydraulic lime-based mortar, comprising the following steps:
[0015] 1) mixing natural hydraulic lime, quartz sand, limestone powder and admixture to obtain a mixture;
[0016] 2) mixing the admixture and water to obtain an admixture mixed solution;
[0017] 3) Add the admixture mixture into the mixture and stir to obtain natural hydraulic lime-based mortar.
[0018] Preferably, in step 3), the stirring speed is 40 to 60 rpm, and the stirring time is 5 to 20 min.
[0019] The present invention also provides the use of the natural hydraulic lime-based mortar in repairing ancient buildings using 3D printing technology.
[0020] Beneficial effects of the present invention:
[0021] The present invention uses natural hydraulic lime as the main component to make mortar, which is highly compatible with the base material of ancient buildings, avoiding the problems of poor compatibility, slow strength development and large drying shrinkage of traditional cement-based materials with ancient buildings. The present invention combines natural hydraulic lime with quartz sand, limestone powder and suitable admixtures and additives to make mortar, which has excellent strength and other properties and is fully suitable for ancient building restoration using 3D printing technology. DETAILED DESCRIPTION
[0022] The present invention provides a natural hydraulic lime-based mortar, which comprises a base material, an admixture, an additive and water;
[0023] The base material comprises the following components in mass fractions: 60-75% of natural hydraulic lime, 15-35% of quartz sand and 5-15% of limestone powder.
[0024] In the present invention, natural hydraulic lime is used as a core material, which can undergo hydration reaction, thereby giving the mortar higher strength and durability; the natural hydraulic lime meets the requirements of EN 459-1:2015 "Building lime - Part 1: Definition specifications and qualification standards"; quartz sand plays the role of aggregate, enhancing the compressive strength and volume stability of the mortar; limestone powder plays a key role in improving the comprehensive performance of the mortar and the simplicity of construction, and can improve the fluidity of the mortar, enhance the adhesion, improve the crack resistance and durability, and optimize the cost structure of the mortar.
[0025] In the present invention, the admixture preferably comprises metakaolin and bentonite, and the mass ratio of metakaolin to base material is preferably 2-5:100, more preferably 3-4:100, and more preferably 3.5:100; the mass ratio of bentonite to base material is preferably 1-3:100, more preferably 1.5-2.5:100, and more preferably 2:100.
[0026] In the present invention, metakaolin can improve the crack resistance, early strength and durability of the mortar, fill the pores of the mortar, and increase the density of the mortar; bentonite is preferably sodium-based bentonite, which plays a role in retaining water and improving the plasticity of the mortar, and helps to control the shrinkage cracks of the mortar.
[0027] In the present invention, the admixture preferably comprises a polycarboxylate water reducer, a redispersible latex powder, wood fiber, starch ether, a thixotropic lubricant and an air entraining agent.
[0028] In the present invention, the polycarboxylate water-reducing agent can improve the fluidity and construction performance of the mortar, while reducing the water-cement ratio and increasing the strength of the mortar; the redispersible latex powder is preferably VAE redispersible latex powder, which can improve the flexibility and bonding performance of the mortar, while enhancing the crack resistance and durability; the wood fiber can enhance the crack resistance and shrinkage resistance of the mortar and prevent the mortar from cracking during the drying process; the starch ether is preferably hydroxypropyl starch ether, which can improve the water retention and construction performance of the mortar and ensure the stability of the construction process; the thixotropic lubricant helps to improve the construction smoothness and anti-segregation of the mortar; the air entraining agent is preferably a powder air entraining agent, which can improve the freeze-thaw resistance of the mortar and reduce the damage to the mortar caused by freeze-thaw cycles.
[0029] In the present invention, the mass ratio of the polycarboxylate water-reducing agent to the base material is preferably 0.1 to 0.3:100, more preferably 0.15 to 0.25:100, and more preferably 0.2:100; the mass ratio of the redispersible latex powder to the base material is preferably 1 to 3:100, more preferably 1.5 to 2.5:100, and more preferably 2:100; the mass ratio of the wood fiber to the base material is preferably 0.5 to 1.5:100, more preferably 0.75 to 1.25:100, and more preferably 1:100; The mass ratio of starch ether to base material is preferably 0.1-0.2:100, more preferably 0.12-0.18:100, and more preferably 0.15:100; the mass ratio of the thixotropic lubricant to base material is preferably 0.2-0.3:100, more preferably 0.22-0.28:100, and more preferably 0.25:100; the mass ratio of the air entraining agent to base material is preferably 0.01-0.05:100, more preferably 0.02-0.04:100, and more preferably 0.03:100.
[0030] In the present invention, the particle size of quartz sand is preferably 100-300 mesh, more preferably 150-250 mesh, and more preferably 200 mesh; the particle size of metakaolin is preferably 500-700 mesh, more preferably 550-650 mesh, and more preferably 600 mesh; the particle size of bentonite is preferably 250-400 mesh, more preferably 300-350 mesh, and more preferably 325 mesh; the length of wood fiber is preferably 0.5-1.5 mm, more preferably 0.7-1.2 mm, and more preferably 1 mm.
[0031] In the present invention, the mass ratio of water to base material is preferably 0.2 to 0.6:1, more preferably 0.3 to 0.5:1, and even more preferably 0.4:1.
[0032] The present invention also provides a method for preparing the natural hydraulic lime-based mortar, comprising the following steps:
[0033] 1) mixing natural hydraulic lime, quartz sand, limestone powder and admixture to obtain a mixture;
[0034] 2) mixing the admixture and water to obtain an admixture mixed solution;
[0035] 3) Add the admixture mixture into the mixture and stir to obtain natural hydraulic lime-based mortar.
[0036] In the present invention, the stirring speed in step 3) is preferably 40 to 60 rpm, more preferably 45 to 55 rpm, and more preferably 50 rpm; the stirring time is preferably 5 to 20 min, and more preferably 10 to 15 min.
[0037] The present invention also provides the use of the natural hydraulic lime-based mortar in repairing ancient buildings using 3D printing technology.
[0038] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.
[0039] The redispersible latex powder used in the embodiments of the present invention is VAE redispersible latex powder, the bentonite is sodium bentonite, the polycarboxylate water reducer is Sika 556P polycarboxylate water reducer, the starch ether is hydroxypropyl starch ether, the wood fiber is German JRS wood fiber ARBOCEL-ZZ8 / 2CA1, the thixotropic lubricant is magnesium aluminum silicate, and the air entraining agent is sodium rosin acid.
[0040] Example 1
[0041] Natural hydraulic lime-based mortar contains base material, admixtures, additives and water.
[0042] The base material comprises the following components in mass fractions: 60% of NHL5 natural hydraulic lime, 35% of quartz sand (with a particle size of 200 meshes), and 5% of limestone powder.
[0043] The admixture comprises metakaolin and sodium bentonite. The particle size of the metakaolin is 600 meshes, and the mass of the metakaolin is 4% of the mass of the base material; the particle size of the sodium bentonite is 325 meshes, and the mass of the sodium bentonite is 1% of the mass of the base material.
[0044] The admixture includes polycarboxylate water-reducing agent, redispersible latex powder, wood fiber, starch ether, thixotropic lubricant and air-entraining agent. The mass of the polycarboxylate water-reducing agent is 0.2% of the mass of the base material, the mass of the redispersible latex powder is 2% of the mass of the base material, the mass of the wood fiber (length is 1 mm) is 0.75% of the mass of the base material, the mass of the starch ether is 0.15% of the mass of the base material, the mass of the thixotropic lubricant is 0.25% of the mass of the base material, the mass of the air-entraining agent is 0.03% of the mass of the base material, and the mass ratio of water to base material is 0.4:1.
[0045] The preparation method of natural hydraulic lime-based mortar is:
[0046] Natural hydraulic lime, quartz sand, limestone powder, metakaolin and sodium bentonite are mixed to obtain a mixture. Polycarboxylic acid water reducer, redispersible latex powder, wood fiber, starch ether, thixotropic lubricant, air entraining agent and water are mixed to obtain an admixture mixture. The admixture mixture is added to the mixture and stirred at a speed of 50 rpm for 10 minutes to obtain a natural hydraulic lime-based mortar.
[0047] Example 2
[0048] Natural hydraulic lime-based mortar contains base material, admixtures, additives and water.
[0049] The base material comprises the following components in mass fractions: 60% of NHL5 natural hydraulic lime, 30% of quartz sand (with a particle size of 200 meshes), and 10% of limestone powder.
[0050] The admixture comprises metakaolin and sodium bentonite. The particle size of the metakaolin is 600 meshes, and the mass of the metakaolin is 4% of the mass of the base material; the particle size of the sodium bentonite is 325 meshes, and the mass of the sodium bentonite is 1.5% of the mass of the base material.
[0051] The admixture includes polycarboxylate water-reducing agent, redispersible latex powder, wood fiber, starch ether, thixotropic lubricant and air-entraining agent. The mass of polycarboxylate water-reducing agent is 0.15% of the mass of the base material, the mass of redispersible latex powder is 2.5% of the mass of the base material, the mass of wood fiber (length is 1 mm) is 1% of the mass of the base material, the mass of starch ether is 0.15% of the mass of the base material, the mass of thixotropic lubricant is 0.3% of the mass of the base material, the mass of air-entraining agent is 0.03% of the mass of the base material, and the mass ratio of water to base material is 0.4:1.
[0052] The preparation method of natural hydraulic lime-based mortar is the same as that of Example 1.
[0053] Example 3
[0054] Natural hydraulic lime-based mortar contains base material, admixtures, additives and water.
[0055] The base material comprises the following components in mass fractions: 65% of NHL5 natural hydraulic lime, 30% of quartz sand (with a particle size of 200 meshes), and 5% of limestone powder.
[0056] The admixture comprises metakaolin and sodium bentonite. The particle size of the metakaolin is 600 meshes, and the mass of the metakaolin is 3.5% of the mass of the base material; the particle size of the sodium bentonite is 325 meshes, and the mass of the sodium bentonite is 1% of the mass of the base material.
[0057] The admixture includes polycarboxylate water-reducing agent, redispersible latex powder, wood fiber, starch ether, thixotropic lubricant and air entraining agent. The mass of the polycarboxylate water-reducing agent is 0.2% of the mass of the base material, the mass of the redispersible latex powder is 2% of the mass of the base material, the mass of the wood fiber (length is 1 mm) is 0.75% of the mass of the base material, the mass of the starch ether is 0.2% of the mass of the base material, the mass of the thixotropic lubricant is 0.25% of the mass of the base material, the mass of the air entraining agent is 0.02% of the mass of the base material, and the mass ratio of water to base material is 0.4:1.
[0058] The preparation method of natural hydraulic lime-based mortar is the same as that of Example 1.
[0059] Example 4
[0060] Natural hydraulic lime-based mortar contains base material, admixtures, additives and water.
[0061] The base material comprises the following components in mass fractions: 65% of NHL5 natural hydraulic lime, 25% of quartz sand (with a particle size of 200 meshes), and 10% of limestone powder.
[0062] The admixture comprises metakaolin and sodium bentonite. The particle size of the metakaolin is 600 meshes, and the mass of the metakaolin is 3.5% of the mass of the base material; the particle size of the sodium bentonite is 325 meshes, and the mass of the sodium bentonite is 1% of the mass of the base material.
[0063] The admixture includes polycarboxylate water-reducing agent, redispersible latex powder, wood fiber, starch ether, thixotropic lubricant and air-entraining agent. The mass of the polycarboxylate water-reducing agent is 0.15% of the mass of the base material, the mass of the redispersible latex powder is 2.5% of the mass of the base material, the mass of the wood fiber (length is 1 mm) is 1% of the mass of the base material, the mass of the starch ether is 0.2% of the mass of the base material, the mass of the thixotropic lubricant is 0.25% of the mass of the base material, the mass of the air-entraining agent is 0.03% of the mass of the base material, and the mass ratio of water to the base material is 0.4:1.
[0064] The preparation method of natural hydraulic lime-based mortar is the same as that of Example 1.
[0065] Example 5
[0066] Natural hydraulic lime-based mortar contains base material, admixtures, additives and water.
[0067] The base material comprises the following components in mass fractions: 70% of NHL5 natural hydraulic lime, 20% of quartz sand (with a particle size of 200 meshes), and 10% of limestone powder.
[0068] The admixture comprises metakaolin and sodium bentonite. The particle size of the metakaolin is 600 meshes, and the mass of the metakaolin is 3% of the mass of the base material; the particle size of the sodium bentonite is 325 meshes, and the mass of the sodium bentonite is 1.5% of the mass of the base material.
[0069] The admixture includes polycarboxylate water-reducing agent, redispersible latex powder, wood fiber, starch ether, thixotropic lubricant and air-entraining agent. The mass of polycarboxylate water-reducing agent is 0.2% of the mass of the base material, the mass of redispersible latex powder is 2.5% of the mass of the base material, the mass of wood fiber (length is 1 mm) is 0.75% of the mass of the base material, the mass of starch ether is 0.15% of the mass of the base material, the mass of thixotropic lubricant is 0.3% of the mass of the base material, the mass of air-entraining agent is 0.02% of the mass of the base material, and the mass ratio of water to base material is 0.4:1.
[0070] The preparation method of natural hydraulic lime-based mortar is the same as that of Example 1.
[0071] Example 6
[0072] Natural hydraulic lime-based mortar contains base material, admixtures, additives and water.
[0073] The base material comprises the following components in mass fractions: 70% of NHL5 natural hydraulic lime, 15% of quartz sand (with a particle size of 200 meshes), and 15% of limestone powder.
[0074] The admixture comprises metakaolin and sodium bentonite. The particle size of the metakaolin is 600 meshes, and the mass of the metakaolin is 3% of the mass of the base material; the particle size of the sodium bentonite is 325 meshes, and the mass of the sodium bentonite is 1.5% of the mass of the base material.
[0075] The admixture includes polycarboxylate water-reducing agent, redispersible latex powder, wood fiber, starch ether, thixotropic lubricant and air-entraining agent. The mass of polycarboxylate water-reducing agent is 0.15% of the mass of the base material, the mass of redispersible latex powder is 2.5% of the mass of the base material, the mass of wood fiber (length is 1 mm) is 1% of the mass of the base material, the mass of starch ether is 0.15% of the mass of the base material, the mass of thixotropic lubricant is 0.25% of the mass of the base material, the mass of air-entraining agent is 0.04% of the mass of the base material, and the mass ratio of water to base material is 0.4:1.
[0076] The preparation method of natural hydraulic lime-based mortar is the same as that of Example 1.
[0077] Example 7
[0078] Natural hydraulic lime-based mortar contains base material, admixtures, additives and water.
[0079] The base material comprises the following components in mass fractions: 75% of NHL5 natural hydraulic lime, 20% of quartz sand (with a particle size of 200 meshes), and 5% of limestone powder.
[0080] The admixture comprises metakaolin and sodium bentonite. The particle size of the metakaolin is 600 meshes, and the mass of the metakaolin is 3% of the mass of the base material; the particle size of the sodium bentonite is 325 meshes, and the mass of the sodium bentonite is 1% of the mass of the base material.
[0081] The admixture includes polycarboxylate water-reducing agent, redispersible latex powder, wood fiber, starch ether, thixotropic lubricant and air entraining agent. The mass of polycarboxylate water-reducing agent is 0.2% of the mass of the base material, the mass of redispersible latex powder is 2% of the mass of the base material, the mass of wood fiber (length is 1 mm) is 0.5% of the mass of the base material, the mass of starch ether is 0.2% of the mass of the base material, the mass of thixotropic lubricant is 0.3% of the mass of the base material, the mass of air entraining agent is 0.03% of the mass of the base material, and the mass ratio of water to base material is 0.4:1.
[0082] The preparation method of natural hydraulic lime-based mortar is the same as that of Example 1.
[0083] Example 8
[0084] Natural hydraulic lime-based mortar contains base material, admixtures, additives and water.
[0085] The base material comprises the following components in mass fractions: 75% of NHL5 natural hydraulic lime, 15% of quartz sand (with a particle size of 200 meshes), and 10% of limestone powder.
[0086] The admixture comprises metakaolin and sodium bentonite. The particle size of the metakaolin is 600 meshes, and the mass of the metakaolin is 3% of the mass of the base material; the particle size of the sodium bentonite is 325 meshes, and the mass of the sodium bentonite is 2% of the mass of the base material.
[0087] The admixture includes polycarboxylate water-reducing agent, redispersible latex powder, wood fiber, starch ether, thixotropic lubricant and air-entraining agent. The mass of polycarboxylate water-reducing agent is 0.15% of the mass of the base material, the mass of redispersible latex powder is 2.5% of the mass of the base material, the mass of wood fiber (length is 1 mm) is 0.75% of the mass of the base material, the mass of starch ether is 0.2% of the mass of the base material, the mass of thixotropic lubricant is 0.25% of the mass of the base material, the mass of air-entraining agent is 0.02% of the mass of the base material, and the mass ratio of water to base material is 0.4:1.
[0088] The preparation method of natural hydraulic lime-based mortar is the same as that of Example 1.
[0089] Comparative Example 1
[0090] The difference from Example 1 is that quartz sand, limestone powder and admixtures are omitted at the same time.
[0091] The mortars of Examples 1 to 8 and Comparative Example 1 were tested for setting time, initial fluidity, compressive strength, flexural strength, interlayer bonding strength, supportability and extrudability. The test results are shown in Table 1.
[0092] The setting time, initial fluidity and compressive strength of the mortar are tested in accordance with EN459-2:2021 "Building Lime-Part 2: Test Methods"; the flexural strength of the mortar is tested in accordance with GB / T 17671-2020; the interlayer bond strength, support and extrudability of the mortar are tested in accordance with TCECS 786-2020.
[0093] Table 1 Mortar performance test results
[0094]
[0095] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A natural hydraulic lime-based mortar, characterized in that: The natural hydraulic lime-based mortar comprises a base material, an admixture, an additive and water; The base material comprises the following components in mass fractions: 60-75% of natural hydraulic lime, 15-35% of quartz sand and 5-15% of limestone powder.
2. The natural hydraulic lime-based mortar according to claim 1, characterized in that: The admixture comprises metakaolin and bentonite, the mass ratio of the metakaolin to the base material is 2-5:100, and the mass ratio of the bentonite to the base material is 1-3:
100.
3. The natural hydraulic lime-based mortar according to claim 2, characterized in that: The admixture comprises a polycarboxylate water reducer, a redispersible latex powder, wood fiber, starch ether, a thixotropic lubricant and an air entraining agent.
4. The natural hydraulic lime-based mortar according to claim 3, characterized in that: The mass ratio of the polycarboxylate water reducer to the base material is 0.1-0.3:100, the mass ratio of the redispersible latex powder to the base material is 1-3:100, the mass ratio of the wood fiber to the base material is 0.5-1.5:100, the mass ratio of the starch ether to the base material is 0.1-0.2:100, the mass ratio of the thixotropic lubricant to the base material is 0.2-0.3:100, and the mass ratio of the air entraining agent to the base material is 0.01-0.05:
100.
5. The natural hydraulic lime-based mortar according to claim 4, characterized in that: The particle size of quartz sand is 100-300 meshes, the particle size of metakaolin is 500-700 meshes, the particle size of bentonite is 250-400 meshes, and the length of wood fiber is 0.5-1.5 mm.
6. The natural hydraulic lime-based mortar according to claim 1, characterized in that: The mass ratio of water to base material is 0.2-0.6:
1.
7. The method for preparing the natural hydraulic lime-based mortar according to any one of claims 1 to 6, characterized in that: The following steps are included: 1) mixing natural hydraulic lime, quartz sand, limestone powder and admixture to obtain a mixture; 2) mixing the admixture and water to obtain an admixture mixed solution; 3) Add the admixture mixture into the mixture and stir to obtain natural hydraulic lime-based mortar.
8. The preparation method according to claim 7, characterized in that: Step 3) The stirring speed is 40 to 60 rpm, and the stirring time is 5 to 20 min.
9. Use of the natural hydraulic lime-based mortar according to any one of claims 1 to 6 in the restoration of ancient buildings using 3D printing technology.
Citation Information
Patent Citations
Filling and binding material composition
CN101844899A